Interleukin 6 at menstruation promotes the proliferation and self-renewal of endometrial mesenchymal stromal/stem cells through the WNT/β-catenin signaling pathway - Li, Tianqi; Li, Raymond H. W.; Ng, Ernest H. Y.; Yeung, William S. B.; Chiu, Philip C. N.; Chan, Rachel W. S. (Frontiers in Immunology, 2024)
Background At menstruation, the functional layer of the human endometrium sheds off due to the trigger of the release of inflammatory factors, including interleukin 6 (IL-6), as a result of a sharp decline in progesterone levels, leading to tissue breakdown and bleeding. The endometrial mesenchymal stem-like cells (CD140b+CD146+ eMSC) located in the basalis are responsible for the cyclical regeneration of the endometrium after menstruation. Endometrial cells from the menstruation phase have been proven to secrete a higher amount of IL-6 and further enhance the self-renewal and clonogenic activity of eMSC. However, the IL-6-responsive mechanism remains unknown. Thus, we hypothesized that IL-6 secreted from niche cells during menstruation regulates the proliferation and self-renewal of eMSC through the WNT/β-catenin signaling pathway. Methods In this study, the content of IL-6 across the menstrual phases was first evaluated. Coexpression of stem cell markers (CD140b and CD146) with interleukin 6 receptor (IL-6R) was confirmed by immunofluorescent staining. In vitro functional assays were conducted to investigate the effect of IL-6 on the cell activities of eMSC, and the therapeutic role of these IL-6- and WNT5A-pretreated eMSC on the repair of injured endometrium was observed using an established mouse model. Results The endometrial cells secrete a high amount of IL-6 under hypoxic conditions, which mimic the physiological microenvironment in the menstruation phase. Also, the expression of IL-6 receptors was confirmed in our eMSC, indicating their capacity to respond to IL-6 in the microenvironment. Exogenous IL-6 can significantly enhance the self-renewal, proliferation, and migrating capacity of eMSC. Activation of the WNT/β-catenin signaling pathway was observed upon IL-6 treatment, while suppression of the WNT/β-catenin signaling impaired the stimulatory role of IL-6 on eMSC activities. IL-6- and WNT5A-pretreated eMSC showed better performance during the regeneration of the injured mouse endometrium. Conclusion We demonstrate that the high level of IL-6 produced by endometrial cells at menstruation can induce the stem cells in the human endometrium to proliferate and migrate through the activation of the WNT/β-catenin pathway. Treatment of eMSC with IL-6 and WNT5A might enhance their therapeutic potential in the regeneration of injured endometrium.